أهمية فهم طبائع العلوم الإسلامية في إعداد الأستاذ المُتخصص فيها وصفاته (Importance of Understanding the Natures of Islamic Sciences In the Preparation of Specialised Lecturer and His Attributes) - برغوث عبد العزيز (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
تتناول الورقة بالدراسة مسألة طبائع العلوم الإسلامية والشرعية، وما يميزها عن غيرها وأثر ذلك على نوعية الأستاذ الجامعي الذي يُدرسها وصفاته وملكاته. وتهدف الورقة إلى بيان هذه الطبائع في تحديد صفات الأستاذ الذي يتعلمها ويُعلمها. ويتبع البحث المنهج الوصفي التحليلي وتحليل النصوص. وخلص البحث إلى أن من طبائع هذه العلوم أنها توحيدية المرجعية، وعملية وعلمية ومنهجية ومقصدية، وتدور حول رسالة الاستخلاف في الأرض واعمارها المتوازن. وعليه فإن الأستاذ الذي يتعلمها ويُعلمها ينبغي أن يتصف بصفات منها: الرسالية والإيمان القوي، والقيادة والإمامية العلمية، والعلم والخبرة، والقدوة النموذجية والحكمة والرشد والتزكية والتطهير. ويوصي البحث بضرورة تطوير برامج تأهيلية متخصصة لأستاذ العلوم الإسلامية والشرعية في الجامعات تراعي واقع التعليم المعاصر، ونوعية المتعلمين وطرق التدريس والتعليم المتلائمة وطبائع هذه العلوم والواقع الذي تُدرس فيه. الكلمات المفتاحية: طبائع العلوم الإسلامية، الأستاذ، الصفات، التعليم الجامعي. Abstract This article analyses the importance of understanding the natures of Islamic sciences, and what distinguishes them from others and the impact of this on the attributes and competencies of the university lecturer who teaches them. The aim of the paper is to show the how these natures influence preparation of the lecturers. The article followed the descriptive analytical method and textual analysis. It concluded that some of the natures of these sciences are: revealed reference, practical, scientific, methodological and purposeful, and revolve around the message of Istikhlaf (vicegerency) and civilisation (umran) on the earth. Accordingly, the teacher who learns and teaches them should have attributes and qualities such as; sense of mission, strong faith, Intellectual leadership, knowledge and experience, exemplary role model, wisdom, guided reasoning, purification and spiritualty. The article recommended the need to develop specialised programs for the lecturers of Islamic and Shari’ah sciences in universities that take into account the realities of contemporary education, the quality of learners, teaching methods and the natures of these sciences. Keywords: Natures of Islamic Sciences, Lecturer, Attributes, University Teaching.